The complete chloroplast genome sequence of Paris nitida G.W.Hu, Z.Wang & Q.F.Wang 2017 (Melanthiaceae), an endemic herb in China - Jinghan Wang; Jiwu Cao; Junsheng Liang; Wei Guo (Mitochondrial DNA. Part B. Resources, 2025)
Paris nitida G.W.Hu, Z.Wang & Q.F.Wang 2017 (Melanthiaceae) is a perennial herb that was first identified in China in 2017. In this study, we determined the circular chloroplast genome of P. nitida through de novo assembly. The 164,734 bp genome exhibits an AT content of 62.89%. We annotated 131 genes, including 36 tRNA genes, eight rRNA genes, and 87 protein-coding genes. Phylogenetic analysis revealed that P. nitida is closely related to Paris fargesii and forms a cluster with Paris dunniana. These findings provide significant genomic information for further research on the evolutionary, taxonomic, and phylogenetic aspects of the genus Paris.